Anti-corruption policy-making, discretionary power, and institutional quality: An experimental analysis - Amadou Boly; Robert Gillanders (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We analyse policy makers' incentives to fight corruption under different institutional qualities. We find that 'public officials', even when non-corrupt, significantly distort anti-corruption institutions by choosing a lower detection probability when this probability applies to their own actions (legal equality), compared to a setting where it does not (legal inequality). As 'public officials' are on average equally corrupt with or without legal equality, an institutional setting with legal equality can be considered worse in reducing corruption. Finally, corruption is significantly lower when the detection probability is exogenously set, suggesting that the institutional power to choose detection can itself be corruptive.
Keywords: C91; D02; D73; D81; 330; anti-corruption; embezzlement; experimental economics; institutions; policy-making